Norway : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Norway. (IMF Staff Country Reports; Country Report ;, 2016)
The paper examines the nature and scale of spillovers to a number of European countries from monetary policies in the euro area and the United States using three different approaches. The analysis focuses on selected non-euro-area countries in Europe: the Czech Republic, Denmark, Hungary, Poland, and Sweden. Recent developments in these countries' sovereign bond yields and exchange rates are indicative of potential spillovers. The paper's most consistent analytical finding is for spillovers to lower domestic bond yields, with the potential for repercussions on credit expansion and asset prices. More recently, the event study uncovered evidence of upward pressure on the exchange rate.